SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PILIHAN PEKERJAAN DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Mahmudi, A. Aviv (potensio, 2013)
Applying the Analytical Hierarchy Process ( AHP ) , required the selection criteria and alternatives , and calculate the weight of a survey questionnaire to decision-makers or users of the system in a place / location associated with the object to be careful . After that , test the consistency necessary to test the validity of the results obtained , and define alternative with the greatest weight as an option . Analytical Hierarchy Process ( AHP ) is able to analyze the selection criteria so as to produce the best ranking in a decision support system determination of employment options . Expert choise is a software that can be used to implement the AHP method . After doing the calculations manually and detail , obtained scores of weight composite PT " A " is greater than the other option , which is 0.3222054 This means, aggregation / combined value of all criteria (Salary , Career , Facilities , Working Environment ) , PT " A " is in first place , followed by PT " D " PT " C " and PT " B " . Based on the criteria weights are implemented through Expert choise , obtained a job selection priority : PT " A " 33.1 % ; PT " D " 28.4 % ; PT " C " 19.8 % ; PT " B " 18.7 %, Because the consistency ratio ( CR ) is 0.01798 , which is â‰¤ 0.1 the calculation of Consistent. Keywords: Analytical Hierarchy Process, Decision Support Systems, specify job options, Expert choise